2013
DOI: 10.1021/nl4000757
|View full text |Cite
|
Sign up to set email alerts
|

Broken Symmetry Quantum Hall States in Dual-Gated ABA Trilayer Graphene

Abstract: ABA-stacked trilayer graphene is a unique 2D electron system with mirror reflection symmetry and unconventional quantum Hall effect. We present low-temperature transport measurements on dual-gated suspended trilayer graphene in the quantum Hall (QH) regime. We observe QH plateaus at filling factors ν = -8, -2, 2, 6, and 10, which is in agreement with the full-parameter tight binding calculations. In high magnetic fields, odd-integer plateaus are also resolved, indicating almost complete lifting of the 12-fold … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 55 publications
4
57
0
Order By: Relevance
“…The ratio between the resistance of the "on" state at high carrier density and the "off" state at the CNP reaches 10 6 at large |D|, which is the largest ratio reported for trilayer graphene. The observed gate dependence of R 23 unambiguously demonstrates the opening of a band gap in the ABC-TG portion of the device.…”
mentioning
confidence: 65%
“…The ratio between the resistance of the "on" state at high carrier density and the "off" state at the CNP reaches 10 6 at large |D|, which is the largest ratio reported for trilayer graphene. The observed gate dependence of R 23 unambiguously demonstrates the opening of a band gap in the ABC-TG portion of the device.…”
mentioning
confidence: 65%
“…This results in a series of QH phase transitions. Note that a similar experiment has been performed by Lee et al [6] but the quantum Hall staircase details were obscured by charge inhomogeneity. This behavior is also observed in device 1-see Fig.…”
mentioning
confidence: 75%
“…The electronic properties of ABA-stacked trilayer graphene (TLG) are being intensively investigated [1][2][3][4][5][6] due to its distinct band structure which consists of two overlapping monolayer-graphene-like (MLG-like) and bilayergraphene-like (BLG-like) bands [1,[7][8][9][10][11][12][13][14]. However, in contrast to MLG and BLG, which are gapless, both subbands in ABA-stacked TLG are gapped, with small masses of the order of a few meV.…”
mentioning
confidence: 99%
“…Subsequent measurements on dual-gated suspended devices by Lee et al 34 observed ν = ±2 plateaus at low magnetic field B < 4 T and also resolved, in high magnetic fields, additional plateaus at ν = ±1, ±3, −4, and −5, indicating almost complete lifting of the 12-fold degeneracy of the LLL. Common to these observations, in particular, is eh asymmetry in the sequence of plateaus, with a prominent ν = −2 plateau.…”
Section: Coulomb Interactionsmentioning
confidence: 82%